The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/sym13101955
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Improving Running Safety of a Railway Wagon with an Independently Rotating Wheel’s Flange

Abstract: The main objective of this work is to study the possibilities of improving the running safety of a railway wagon with independently rotating wheels by changing their design symmetrically mounted on an axle. The article provides a discussion of the advantages and disadvantages of using the independently rotating wheels in a bogie of railway wagons. Their increasing tendency of derailment is described. The influence of a perspective constructive scheme (PKS) of railway wagon wheels in comparison with a tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…To investigate the effects of the PKS wheel design on running resistance, various studies have been conducted. These studies have revealed that the PKS wheel design has a positive impact not only on the wear of the wheel/rail surfaces and noise reduction but also on the overall running safety of the railway vehicle 47 .…”
Section: The State Of the Art Of Railway Vehicles Equipped With Indep...mentioning
confidence: 99%
“…To investigate the effects of the PKS wheel design on running resistance, various studies have been conducted. These studies have revealed that the PKS wheel design has a positive impact not only on the wear of the wheel/rail surfaces and noise reduction but also on the overall running safety of the railway vehicle 47 .…”
Section: The State Of the Art Of Railway Vehicles Equipped With Indep...mentioning
confidence: 99%
“…The percentage of low floor occupancy in a tram vehicle may vary and depends on, inter alia, the requirements formulated by the contracting authority or the condition of the track infrastructure on which the tram vehicle is to be operated [37,38].…”
Section: Design Solutions Of the Drive System Depending On The % Of L...mentioning
confidence: 99%
“…System failures in suburban and urban transport operations of industrial, scientific and educational centers result in a rapid increase in transportation time expenditures, material resource consumption, the number of road traffic incidents, and environmental degradation. In the literature, many scientific and research works have been devoted to these issues, for example: [9,10,16,20]. In particular, the issues of transport safety are presented in [17,30] and concerning the impact on the natural environment in [7,33] and operation costs and transportation quality [14,15].…”
Section: Introductionmentioning
confidence: 99%